Enhancement of plume dilution in two‐dimensional and three‐dimensional porous media by flow focusing in high‐permeability inclusions. Issue 7 (25th July 2015) - Ye, Yu; Chiogna, Gabriele; Cirpka, Olaf A.; Grathwohl, Peter; Rolle, Massimo
Abstract In porous media, lateral mass exchange exerts a significant influence on the dilution of solute plumes in quasi steady state. This process is one of the main mechanisms controlling transport of continuously emitted conservative tracers in groundwater and is fundamental for the understanding of many degradation processes. We investigate the effects of high‐permeability inclusions on transverse mixing in three‐dimensional versus two‐dimensional systems by experimental, theoretical, and numerical analyses. Our results show that mixing enhancement strongly depends on the system dimensionality and on the parameterization used to model transverse dispersion. In particular, no enhancement of transverse mixing would occur in three‐dimensional media if the local transverse dispersion coefficient was uniform and flow focusing in both transverse directions was identical, which is fundamentally different from the two‐dimensional case. However, the velocity and grain size dependence of the transverse dispersion coefficient and the correlation between hydraulic conductivity and grain size lead to prevailing mixing enhancement within the inclusions, regardless of dimensionality. We perform steady state bench‐scale experiments with multiple tracers in three‐dimensional and quasi two‐dimensional flow‐through systems at two different velocities (1 and 5 m/d). We quantify transverse mixing by the flux‐related dilution index and compare the experimental results with model simulations. The experiments confirm that, although dilution is larger in three‐dimensional systems, the enhancement of transverse mixing due to flow focusing is less effective than in two‐dimensional systems. The spatial arrangement of the high‐permeability inclusions significantly affects the degree of mixing enhancement. We also observe more pronounced compound‐specific effects in the dilution of solute plumes in three‐dimensional porous media than in two‐dimensional ones.